The Revised WIC Food Package and Child Development: A Quasi-Experimental Study - Guan, Alice; Hamad, Rita; Batra, Akansha; Bush, Nicole R; Tylavsky, Frances A; LeWinn, Kaja Z (Pediatrics (Evanston), 2021)
The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), one of the largest US safety net programs, was revised in 2009 to be more congruent with dietary guidelines. We hypothesize that this revision led to improvements in child development. Data were drawn from a cohort of women and children enrolled in the Conditions Affecting Neurocognitive Development and Learning in Early Childhood study from 2006 to 2011 (Shelby County, TN; = 1222). Using quasi-experimental difference-in-differences analysis, we compared measures of growth, cognitive, and socioemotional development between WIC recipients and nonrecipients before and after the policy revision. The revised WIC food package led to increased length-for-age scores at 12 months among infants whose mothers received the revised food package during pregnancy (β = .33, 95% confidence interval: 0.05 to 0.61) and improved Bayley Scales of Infant Development cognitive composite scores at 24 months (β = 4.34, 95% confidence interval: 1.11 to 7.57). We observed no effects on growth at age 24 months or age 4 to 6 years or cognitive development at age 4 to 6 years. This study provides some of the first evidence that children of mothers who received the revised WIC food package during pregnancy had improved developmental outcomes in the first 2 years of life. These findings highlight the value of WIC in improving early developmental outcomes among vulnerable children. The need to implement and expand policies supporting the health of marginalized groups has never been more salient, particularly given the nation's rising economic and social disparities.